2020
DOI: 10.1111/crj.13159
|View full text |Cite
|
Sign up to set email alerts
|

The utility of elastography during EBUS‐TBNA in a population with a high prevalence of anthracosis

Abstract: BackgroundUltrasound elastography, is a pioneer sonographic modality that is conducted during endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) in order to increase the accuracy of sampling location. The current study aims to evaluate the usefulness of elastography during EBUS‐TBNA in a population with a high prevalence of anthracosis.MethodsThis prospective single‐blinded study was performed on 69 lymph nodes (LNs) of patients with mediastinal lymphadenopathy undergoing EBUS‐TBNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…calci cation or necrosis in the lymph nodes (He et al 2017). False positive results have been reported in previous studies, mostly due to the increased stiffness in tuberculosis, pneumoconiosis, or sarcoidosis (Abedini et al 2020;Dong et al 2018;Trisolini et al 2020) (Livi et al 2019). In our study, we observed that 6 cases had blue images in elastography, however, the nal pathological diagnosis were calci cation or brosis in the lymph nodes.…”
Section: Discussionsupporting
confidence: 44%
“…calci cation or necrosis in the lymph nodes (He et al 2017). False positive results have been reported in previous studies, mostly due to the increased stiffness in tuberculosis, pneumoconiosis, or sarcoidosis (Abedini et al 2020;Dong et al 2018;Trisolini et al 2020) (Livi et al 2019). In our study, we observed that 6 cases had blue images in elastography, however, the nal pathological diagnosis were calci cation or brosis in the lymph nodes.…”
Section: Discussionsupporting
confidence: 44%
“…15,17,19,20 In this study, all six benign LNs with a SAR >0.6 were found in patients with a history of pulmonary tuberculosis or apparent exposure to mineral dusts such as coal or asbestos. The effectiveness of EBUS elastography has been reported in a population with a high prevalence of anthracosis 32 ; however, the effects of other occupational inhalation exposures and a prior history of pulmonary tuberculosis on EBUS elastography remain poorly studied. It is important for bronchoscopists to acknowledge that a patient's occupational and medical history may affect the results of EBUS elastography; therefore, careful review and modification of the SAR cutoff value, based on each individual patient's history, are necessary.…”
Section: Figurementioning
confidence: 99%
“…One study on EBUS elastography was excluded due to lack of sufficient information to verify and extract the true positive, FP, false negative, and true negative values required for summary statistics of diagnostic accuracy. 20…”
Section: Resultsmentioning
confidence: 99%